Migração e identidade : formação de comunidades evangélicas nas colonizações mistas de Três de Maio, Horizontina e Dr. Maurício Cardoso de 1915 a 1950 - Froemming, Angela Brandalise (2009)
In the present essay I aim at to investigate and tell as occurred the formation of the evangelical communities from Três de Maio, Horizontina and Dr. Maurício Cardoso in the State of Rio Grande do Sul in a perspective of ethnic identity front to the Brazilian nationalism motion in the first half of twentieth century. The first part, approaches concepts referring to the ethno, nation, region and as these concepts relate in a plural society. It works with concepts that referring to historical memory: individual and collective and methods of oral history. In the second part, it does a brief revision on immigration and formation of the first evangelical communities in the Rio Grande do Sul, in a perspective of ethnic identity in assimilation process to "the adoptive" nation. We see the efforts of parsons and communities to keep the (teuto)-evangelical immigrants persevering in their faith and later the consolidation of a Synod that established connection the different parishes and existing communities in the state of the Rio Grande do Sul in nineteenth century and beginning of twentieth century. Also it approaches the politics facts of Brazil and the world that had influenced in the process of assimilation of the (teuto)-evangelical element to the Brazilian society and as it developed the questions of Germanic ethno versus Brazilian nationalism. In the third part of this study are told the facts that occurred in the foundation and the first years of existence of the evangelical communities in Três de Maio, Horizontina and Dr. Maurício Cardoso. About the identity perspective, we analyze formation of the evangelical communities in a context of multiethnic society, which were the mixing colonization promoted by the state government of Borges de Medeiros at the beginning of twentieth century. We analyze the existing relations among the (teuto)-evangelical with other ethnic minorities and religious denominations, as well as the repression suffered during the dictatorship of Getúlio Vargas (from 1942). We see as the identity of the evangelical was being influenced by the Campaign of Nationalization getting the formation of a new identity from the end of Second World War (1945)